2000
DOI: 10.1016/s0165-0270(00)00302-2
|View full text |Cite
|
Sign up to set email alerts
|

Complex brain circuits studied via simultaneous and permanent detection of three transported neuroanatomical tracers in the same histological section

Abstract: Experimental neuroanatomical tracing methods lie at the basis of the study of the nervous system. When the scientific question is relatively straightforward, it may be sufficient to derive satisfactory answers from experiments in which a single neuroanatomical tracing method is applied. In various scientific paradigms however, for instance when the degree of convergence of two different projections on a particular cortical area or subcortical nucleus is the subject of study, the application of single tracing m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…Confirming its documented utility as an anterograde tracer (Veenman et al, 1992;Wouterlood and JorritsmaByham, 1993;Lanciego et al, 2000;Reiner et al, 2000), we found that BDA-10,000 provided discrete labeling of BF cell bodies and reliable anterograde labeling of BF fibers and varicosities. Although we noticed some labeled cells in areas surrounding the injection site in the MCPO-SI, which might have been retrogradely labeled, we did not find cells retrogradely labeled at a distance in the prefrontal cortex or LH, confirming that BDA-10,000, in contrast to BDA-3000 MW, results in neglible retrograde labeling (Wouterlood and Jorritsma-Byham, 1993;Reiner et al, 2000).…”
Section: Technical Considerationssupporting
confidence: 77%
See 1 more Smart Citation
“…Confirming its documented utility as an anterograde tracer (Veenman et al, 1992;Wouterlood and JorritsmaByham, 1993;Lanciego et al, 2000;Reiner et al, 2000), we found that BDA-10,000 provided discrete labeling of BF cell bodies and reliable anterograde labeling of BF fibers and varicosities. Although we noticed some labeled cells in areas surrounding the injection site in the MCPO-SI, which might have been retrogradely labeled, we did not find cells retrogradely labeled at a distance in the prefrontal cortex or LH, confirming that BDA-10,000, in contrast to BDA-3000 MW, results in neglible retrograde labeling (Wouterlood and Jorritsma-Byham, 1993;Reiner et al, 2000).…”
Section: Technical Considerationssupporting
confidence: 77%
“…Confirming the utility of BDA as an anterograde tracer that can be readily used along with immunostaining for elucidating complex neural circuits (Lanciego et al, 2000), we were able to apply double staining for BDA and the VTPs in order to identify the neurotransmitters utilized by the BF neurons projecting to the LH. We found that with the use of Triton (0.1%), we obtained complete penetration in material double stained for VTP antibodies and streptavidin (through 25-m-thick sections).…”
Section: Technical Considerationsmentioning
confidence: 78%
“…On the other hand, BDA10k is highly recommended as an anterograde tracer, and it does yield some retrograde labeling [Reiner et al, 2000, and references therein]. Other benefits of BDA10k are that it might be combined with established retrograde tracers, such as cholera toxin B and Fluoro-Gold [Coolen and Wood, 1998;Coolen et al, 1999;Lanciego et al, 2000], and that BDA tracing at ultrastructural level is also possible, in particular in combination with transmitter immunocytochemistry [Pickel et al, 1996;Reiner et al, 2000;Miyashita et al, 2007]. We confirm that BDA10k might be the tracer of choice for anterograde tracing experiments.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Typically tracers injected into the brain enter neurons locally and are picked up by the intracellular transport machinery and then carried along neuronal processes to reach distant synapses or cell bodies (Fritzsch, 1993;Grafstein and Forman, 1980;Lanciego et al, 2000). Transport from the synapse back to the cell body is termed "retrograde," and from the cell body towards the synapse "anterograde".…”
Section: Introductionmentioning
confidence: 99%